Study Experimental The Effect of CaCO3 and Fe2O3 Mass Composition Ratio on Calcium Ferrite Phase Formation Base on Local Materials Iron Sand and Limestone - Mastuki Mastuki; AW Brata; AG Istiawan; B Aditya; H Masrufi (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2020)
Iron sand contains Fe3O4 which can be produced Fe2O3 and limestone contains dominant CaCO3. Both of these materials are very abundant in Indonesia. Iron sand is generally used as building construction materials, as well as the use of limestone, there has been no development in the management of the combination of the two materials. Because of the abundance of iron sand and limestone which have not yet been developed to the fullest, a study was carried out to manage and develop the product as a follow up to the previous Calcium Ferrite research. This research focuses on analyzing the phase of Calcium Ferrite formed using XRD and SEM-EDX tests. Tests were carried out on samples with a mass ratio of a mixture of Fe2O3 and CaCO3 of 1: 4, 1: 6, 1: 8, and 1:12. The XRD test results showed that the phases formed were dominated by the Ca2Fe2O5 and Ca2Fe9O13 phases. And from the SEM-EDX test results, the results indicate the formation of nano-scale Calcium Ferrite with the composition of elements Ca, Fe, O, and Si.